Existence of Positive Solutions for Nonlinear Eigenvalue Problems. (8th March 2010) - Wang, Sheng-Ping; Wong, Fu-Hsiang; Kung, Fan-Kai
Abstract : We use a fixed point theorem in a cone to obtain the existence of positive solutions of the differential equation, u ″ + λ f ( t, u ) = 0, 0 < t < 1, with some suitable boundary conditions, whereλ is a parameter.